A dedicated place for volume fraud within the current UK economic crime agenda?: The Greater Manchester police case study. Issue 4 (3rd October 2016) - King, Julian; Doig, Alan
Abstract : Purpose: The purpose of this study is to explore how a large UK police force – Greater Manchester Police (GMP) – sought during a period of continuing budget reductions to take a cost-effective approach to certain types of fraud through the establishment of a central Volume Fraud Team (VFT), which in turn would also have wider operational resource benefits across the force. It then explores the decision to merge that team with its existing serious and complex fraud team. Design/methodology/approach: The research was undertaken over a period of two years by interview and desk review to explain the internal processes which underpinned the approach and the initial outcomes. It discusses why the approach was short lived as a consequence of other factors. Findings: The paper sets out briefly the context of changes to the policing of fraud since 1979 and describes the GMP decision-making processes that established a centralised response to volume fraud and major (serious and complex) fraud. The paper assesses the available data on the approach and whether the changes facilitated a more effective means of addressing fraud and other internal policing priorities. It then discusses the decision in 2014 to merge the staff resources for volume and major frauds in response to identified policy trends in fraud investigations and changes in fraud reporting. Research limitations/implications: The single case study is limited in terms of focus and in applicability to the wider law enforcement response to fraud. Practical implications: The research discusses practitioner issues arising from the complexities of balancing resources and priorities against changing trends and patterns of criminal activity in a specific area of policing. Originality/value: The research is an original study into the internal and external change agendas, and there are, therefore, wider lessons for the policing of fraud in the UK.